2021
DOI: 10.31234/osf.io/hkt5a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inclusion of the other in the self as a potential risk factor for prolonged grief disorder: A comparison of patients with matched bereaved healthy controls

Abstract: Pathological grief has received increasing attention in recent years, as about A10% of the bereaved suffer from one kind it. Pathological grief in the form of Prolonged grief disorder (PGD) is a relatively new diagnostic category which has been introduced into the ICD-11 beta version in 2018. To date, various risk and protective factors, as well as treatment options for pathological grief, have been proposed. Nevertheless, empirical evidence in that area is still scarce. Our aim was to identify the impact inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Combined with the results obtained from the IIP‐D, it could be argued that the cooperation behavior in the FIPD is the result of warm‐submissive behavior and the underlying will to please others, however, interpreting the group × repeated measures interaction, which demonstrated that the number of shared tokens tended to be distributed differently across the 30 trials for the two groups, could also indicate a lack of social flexibility (Nelson & Guyer 2011) due to deficient valuation, inhibition, or rule use. Without further evidence, we suggest that valuation may be most deficient in PGD, leading to stronger commitment, higher dependency, and a higher than normal tendency to feel fused with the bereaved, as shown by other studies (Harrison et al 2021). Hence, in persistently over‐valuating the other, they might lack the capability to adapt to changes in the relationship.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Combined with the results obtained from the IIP‐D, it could be argued that the cooperation behavior in the FIPD is the result of warm‐submissive behavior and the underlying will to please others, however, interpreting the group × repeated measures interaction, which demonstrated that the number of shared tokens tended to be distributed differently across the 30 trials for the two groups, could also indicate a lack of social flexibility (Nelson & Guyer 2011) due to deficient valuation, inhibition, or rule use. Without further evidence, we suggest that valuation may be most deficient in PGD, leading to stronger commitment, higher dependency, and a higher than normal tendency to feel fused with the bereaved, as shown by other studies (Harrison et al 2021). Hence, in persistently over‐valuating the other, they might lack the capability to adapt to changes in the relationship.…”
Section: Discussionsupporting
confidence: 56%
“…However, studies have shown that PGD is associated with insecure attachment and that PGD patients often have formed a very close, almost dependent relationship with the deceased, which makes it difficult for them to form new relationships (Burke & Neimeyer 2013; Maccallum & Bryant 2018; Mancini et al 2015). In fact, PGD patients have been found to feel significantly closer to the deceased than to their closest living friend, and to experience higher than normal identity fusion with the deceased (Harrison et al 2021). Such higher self‐other fusion is associated with more empathy and altruism (Cialdini et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation